THE INFLUENCE OF INTELLECTUAL CAPITAL ON COMPANY VALUE WITH PROFITABILITY AS A MODERATION VARIABLE - Tulus Pujo Nugroho (International Journal Multidisciplinary Science, 2023)
This aim is to investigate the impact of Intellectual Capital on Company Value by considering the Profitability factor as a moderator variable in Hospitality Sub-Sector Companies during the 2012-2016 period. The independent variables in this study were measured using VAICTM which was approximated by Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The dependent variable in this research is Company Value which is measured through PBV, while the moderating variable is Profitability which is measured by Return On Assets (ROA). Data analysis was carried out using Multiple Regression and Moderating Regression Analysis (MRA) techniques using the SPSS for Windows 16.0 program. The results of this research reveal that (1) Intellectual Capital (VAICTM) does not have a significant negative impact on Company Value (PBV). From the t test results, VACA has no partial and insignificant positive effect on PBV. VAHU does not have a partial and significant negative effect on PBV. STVA has no partial and insignificant positive effect on PBV. (2) Return on Assets (ROA) has a negative effect in moderating the relationship between Intellectual Capital and Company Value